1981
DOI: 10.3758/bf03202358
|View full text |Cite
|
Sign up to set email alerts
|

Expectancy and frequency effects on perceptual and motor systems in choice reaction time

Abstract: Three experiments investigated the effects of expectancy and stimulus frequency in character classification and identification tasks. Both expectancy and frequency were found to have effects on overall response latency, but the two factors had different patterns of interaction with two other experimental variables. The effect of visual quality was larger for low-frequency stimuli than for high-frequency stimuli, whereas the effect of quality was independent of expectancy. The effect of S-R compatibility was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Specifically, the effects of both probability and sequence should be greater at the low level of luminance. An additive relation between sequence and luminance would be evidence against the proposal of a sequential mechanism for the probability effect at encoding, and would thus be consistent with Miller and Anbar's (1981) proposal of a gradual practice mechanism for the effect. …”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Specifically, the effects of both probability and sequence should be greater at the low level of luminance. An additive relation between sequence and luminance would be evidence against the proposal of a sequential mechanism for the probability effect at encoding, and would thus be consistent with Miller and Anbar's (1981) proposal of a gradual practice mechanism for the effect. …”
mentioning
confidence: 71%
“…These results suggest that the probability effect on perceptual processing is not an indirect result of sequential effects. Together with the results of Miller and Anbar (1981), they suggest that practice gradually acts to facilitate the perceptual processing of highly probable stimuli. …”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Del Fava and Ribeiro-do-Valle (2004) specifically tested this hypothesis and could not confirm it. Instead, their results indicated that temporal expectancy, defined as the attentional process generated by widespread networks of frontal, parietal and limbic areas (see Coull et al, 2000, andEngel et al, 2001) which produces a time dependent increase in the excitability of a specific sensorimotor circuit (Jennings, Van der Molen, & Steinhauer, 1998;Miller & Anbar, 1981; see, for a review, Sanders, 1966, Van der Heijden, 1992, and Nobre, Correa, & Coull, 2007, is most likely responsible for the effect. This process was named automatic (unintentional) temporal expectation by Nobre et al (2007), because it is automatically mobilized by the auditory prime stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…It occurs immediately after the WS and has a relatively short duration. Temporal expectancy is most commonly referred to as a process that induces a time-dependent increase in the excitability of a specific sensorimotor circuit (Jennings, Van der Molen, & Steinhauer, 1998;Miller, & Anbar, 1981;Sanders, 1966;Sullivan, Urakawa, & Cossey, 1996;Van der Heijden, 1992). It strongly depends on the relative probability of the occurrence of a relevant event at each moment.…”
Section: Introductionmentioning
confidence: 99%